PROVIDING EDUCATION WITH LEAFLETS REGARDING BABY CARE TO PREGNANT WOMEN - Lubis, Dina Putri Utami; Mita Meilani; Wulandari, Risky Puji (Jurnal Pengabdian Masyarakat Permata Indonesia, 2023)
Background: Baby care is a series of actions and practices carried out to meet the physical, emotional and developmental needs of babies so that they grow and develop healthily. Baby care includes various aspects such as hygiene care, meeting nutritional needs, sleep care, sensory stimulation, skin care, health management, and emotional support. Handling and caring for newborn babies at home requires adequate knowledge and skills. Therefore, it is important for mothers to prepare themselves as best as possible before caring for a newborn baby at home so that they can fulfill the baby's rights in the form of optimal love, care and nurturing. The intervention of providing education through leaflet media was chosen because leaflets are one of the pamphlet type information media that is available. most popular. The aim of this service is to analyze the effect of educational media using leaflets on the ability to care for babies in pregnant women. Method: This community service takes the form of providing education with leaflets regarding baby care for pregnant women in Banyuraden Gamping Village, using a science-based method, an approach that involves the community, is persuasive and educational. Conclusion: there is an influence of providing education through leaflet media on increasing knowledge of baby care in pregnant women.